How Marketing Mumbo Jumbo Can Help Poor Countries Grow: The Case of 100% Columbian Coffee - Marti, Rafael (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This work starts with an overview of the consequences of falling prices in manufactures for developing countries and the role marketing and country branding can play in promoting exports to high income countries, where differentiated products are sold with high margins. To understand how branding works, the second chapter presents a summary of scientific findings regarding the psychological dimension of branding, focusing on the role emotions play; it also analyses the main traits of today's branding. Building upon this framework, chapters III and IV, review the case of the 100% Colombian Coffee campaign, and examine its brand equity, history, and recent development. As a conclusion, some guidelines are given to poor countries in order to take advantage of marketing techniques when exporting to the US and Europe.